Fatigue crack growth in steel beams strengthened by CFRP strips. (October 2016) - Colombi, Pierluigi; Fava, Giulia
Highlights: Fatigue performance of cracked steel beams under constant amplitude cycling loads was explored. Fatigue repair of cracked steel beams with CFRP plates bonded to the tension flange was studied. Debonding of the CFRP reinforcement from the cracked steel beams was investigated. Analytical models were developed to predict the fatigue crack growth curves. Abstract: The present paper investigates the fatigue crack growth of steel beams strengthened by using Carbon Fibre Reinforced Polymers (CFRP) from the experimental and analytical point of view. Artificially cracked steel beams were reinforced at the bottom side of the tension flange by applying CFRP strips bonded with epoxy adhesive. Different reinforcement arrangements were considered (i.e., single and double reinforcement layer) and the specimens were tested under a four-point bending configuration. Then, an analytical model was proposed to predict the strain redistribution in the reinforcement strips and the fatigue crack growth curves. Experimental evidence showed the presence of a debonded area between the reinforcement and the steel beam at the crack location. In detail, for the double reinforcement case, this caused a noticeable scatter of the fatigue crack growth curves. Finally, a good agreement was found between the analytical results and the experimental ones, in terms of both the strain distribution in the CFRP and fatigue crack growth curves.